Comparison of Cultures from Rectoanal-Junction Mucosal Swabs and Feces for Detection of Escherichia coli O157 in Dairy Heifers - Davis, Margaret A. (American Society for Microbiology, 2006)
Fecal culture for Escherichia coli O157:H7 was compared to rectoanal mucosal swab (RAMS) culture in dairy heifers over a 1-year period. RAMS enrichment culture was as sensitive as fecal culture using immunomagnetic separation (IMS) (P = 0.98, as determined by a chi-square test). RAMS culture is less costly than fecal IMS culture and can yield quantitative data.